1969
DOI: 10.1128/jb.99.1.175-179.1969
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Studies on the Structure of Mucopeptide Isolated from Streptococcus bovis

Abstract: Mucopeptides isolated from Streptococcus bovis cell walls were found to be composed of alanine, glutamic acid, lysine, and threonine in a mole ratio of 3 :1:1:1. A dipeptide, NE-lysylthreonine, was isolated from S. bovis mucopeptide by ion-exchange chromatography. This finding suggests that threonine is associated with the bridge which cross-links adjacent tetrapeptides by connecting the e-amino group of lysine of one tetrapeptide to the carboxyl group of D-alanine of another to form the mucopeptide matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

1972
1972
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
3
6
0
Order By: Relevance
“…This type was first described by Schleifer and Kandler (336) for a Streptococcus which was most probably wrongly delineated as S. cremoris (Hladny, Ph.D. thesis, Technical University, Munich, 1971). Almost the same type was found in S. bovis (179), in some strains of S. equinus, and in a strain of S. milleri (14a); the only difference is that some of the Ala residues in the interpeptide bridges are replaced by Ser. In one strain of S. equinus, in two strains of S. milleri, and in S. salivarius II (not reacting w^ith an-BACTERIOL REV.…”
Section: Gram-negative Bacteriasupporting
confidence: 53%
“…This type was first described by Schleifer and Kandler (336) for a Streptococcus which was most probably wrongly delineated as S. cremoris (Hladny, Ph.D. thesis, Technical University, Munich, 1971). Almost the same type was found in S. bovis (179), in some strains of S. equinus, and in a strain of S. milleri (14a); the only difference is that some of the Ala residues in the interpeptide bridges are replaced by Ser. In one strain of S. equinus, in two strains of S. milleri, and in S. salivarius II (not reacting w^ith an-BACTERIOL REV.…”
Section: Gram-negative Bacteriasupporting
confidence: 53%
“…In addition to these amino acids, threonine (0.71-0.75 mole) was found in HS-1 (a) , OMZ65 (g) , and AHT (g) cell walls; and aspartic acid (0.37 mole) in OMZ176 (d) and OMZ65 (g) cell walls. Acid hydrolysates of HS-1 (a) cell walls, unlike the other strains, yielded a ninhydrin-positive peak between glucosamine and lysine, which was reported by other investigators to be a dipeptide composed of lysine and threonine (20,42,45). Trace amounts (less than 0.1 mole) of various amino acids other than those listed in Table 2 were also detected in all the cell wall preparations.…”
Section: Lysis Of Cell Wallssupporting
confidence: 65%
“…These two serotypes have also been shown to be closely related to each other in serological reactivity (12,16,26,38). The cell wall peptidoglycan of Streptococcus cremoris (42), Streptococcus bovis (18,20,45), Streptococcus equinus (45), and Micrococcus roseus (39) has been reported to contain threonine which is involved in the cross-linking of the adjacent peptide chain between the s-amino group of lysine and the carboxyl group of a C-terminal D-alanine. It has been found that threonine is linked to lysine in the cell walls of S. cremoris (42) and S. bovis (20,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slade and Slamp (15) employed the differences in peptidoglycan composition as a criterion to classify the various streptococci into different groups. Kane et al (7) reported in detail the complete structure of mucopeptides from Streptococcus bovis. Kolenbrander and Ensign (9) reported a detailed study on the peptidoglycan structure and composition of Spirillum serpens.…”
mentioning
confidence: 99%